Collective contracts, wages and wage diepersion in a multi-level model - Gesine Stephan; Knut Gerlach (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2004)
The authors use German linked employer-employee data for the years 1990, 1995 and 2001 to analyze, which dimensions of wage setting differ across three wage-setting regimes: Establishments applying sectoral collective contracts, establishments with firm-level contracts and uncovered establishments. The empirical analysis is restricted to workers without supervisory functions in larger manufacturing firms and shows that for this group of workers base wages are higher in firms applying collective contracts, while returns to human capital and the gender wage gap are reduced. Moreover, during the nineties these effects have become stronger.
Keywords: J31; J51; 330; Tarifvertrag; Lohnstruktur; Lohnfindung; Flächentarifvertrag; Firmentarifvertrag; Tariflohn; Lohnhöhe; geschlechtsspezifische Faktoren